CCAFS Program Management Committee and the Independent Science Panel visit to Nyando Climate-Smart Villages - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
On 7th May 2015 The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), East Africa hosted the program’s Independent Science Panel (ISP) and Program Management Committee (PMC) at the Nyando Climate-Smart Villages in Kenya, one of the region’s learning sites. The team visited farmers to see the uptake of various climate- smart technologies that have made them food secure and increased their adaptive capacity to climate variability. The climate –smart farmers have not only increased their yields but have also become champion farmers (examples) for the community to emulate. Photos: V.Atakos and S.Kilungu (CCAFS).